Congenital heart disease in the teenage patient - Day, Thomas G.; Adwani, Satish (Paediatrics and child health, 2018)
Due to increasing incidence and improved survival, greater numbers of children with congenital heart disease (CHD) are surviving to their teenage years and beyond. This patient group have complex medical needs that interact with the emotional and developmental challenges of adolescence. Teenagers with CHD are at increased risk of both neurodevelopmental and emotional disorders. Quality of life is also significantly impaired in this group, and strategies should be considered to maximise this and other holistic outcomes. As teenage patients become adults, their care is transitioned to adult services, a potentially stressful time for these patients. It is important that this process is well understood, and managed in a streamlined and organised manner to minimise numbers lost to follow-up. It is at this stage that patient educational information, probably previously given to parents or carers, is reiterated to the patient themselves. This should include advice around the patient's specific lesion, as well as general advice about exercise tolerance, endocarditis risk, and pregnancy.